Understanding Child Malnutrition Reduction in Indonesia Children Aged 0‒19 Years: A Linear Decomposition Approach - Kunto, Yohanes Sondang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study examines child malnutrition reduction in Indonesia and whether it was due to improved nutrition in younger cohorts or reversal of malnutrition in older cohorts. Data were from five Indonesian Family Life Survey (IFLS) waves 1993–2015, comprising 59,973 observations from 29,073 children aged 0–19 years. This study used logit models to perform linear decomposition. The results show cohort replacement (AOR=0.992, p<0.01) and intracohort change (AOR=0.979, p<0.01) reduce stunting. However, these effects do not protect younger cohorts from being overweight (AOR=1.073, p<0.01) or prevent older cohorts from thinness (AOR=1.009, p< 0.01). In conclusion, there are cohort effects on child malnutrition reduction in Indonesia.